Thrombophilia screening in women with recurrent first trimester miscarriage: is it time to stop testing? – a cohort study and systematic review of the literature. Issue 7 (13th July 2022) - Shehata, Hassan; Ali, Amanda; Silva-Edge, Mariane; Haroon, Shahla; Elfituri, Abdullatif; Viswanatha, Radhika; Jan, Haider; Akolekar, Ranjit
Abstract : Objective: There are numerous studies reporting a disproportionally high prevalence of thrombophilia in women with a history of recurrent miscarriage (RM), which has led to overdiagnosis and treatment without an improvement in clinical outcomes. The objective of our study was to assess the prevalence of inherited and acquired thrombophilia in a large cohort of women with a history of early RM using internationally agreed diagnostic criteria and inclusion parameters and compare it to the meta-analysis results of existing literature. Methods: Design: Retrospective cohort study and systematic review of literature. Setting: This is a retrospective cohort study set-up in two dedicated tertiary centres for women with RM in Southwest London and Surrey. We reviewed all the available literature related to causes of RMs. We ascertained the prevalence of thrombophilia in the study population and compared it with historical and published prevalence in the general population. Participants: 1155 women between 2012 and 2017. All patients had three or more first trimester miscarriages and a full thrombophilia screen. Results: The overall prevalence of thrombophilia in our study population is 9.2% (106/1155) with 8.1% (94/1155) of cases positive for inherited thrombophilia, which is similar to the general population; Factor V Leiden (4.9%; 57/1155) and prothrombin gene mutation (2.9%; 34/1155) were the most common inherited thrombophilias, while only 1% (12/1155) tested positive for acquired thrombophilia. Persistent positive lupus anticoagulant (LA) was found in 0.5% (6/1155) and persistent positive anticardiolipin (ACL) antibodies with a value ≥40 U/mL was found in 0.5% (6/1155) of patients. Tests for LA/ACL were performed a minimum of 12 weeks apart thus meeting the revised Sapporo criteria for a diagnosis of antiphospholipid syndrome. Conclusion: The findings of our study demonstrate that the prevalence of inherited thrombophilia is similar in women with RM to that in the general population. Similarly, the prevalence of acquired thrombophilia, using the revised Sapporo criteria, in the cohort of RMs is similar to that in the general population. Therefore, we do not recommend investigation or treatment of inherited or acquired thrombophilia in women with RM. PROSPERO registration number: CRD42020223554.